Highway and Urban Environment Proceedings of the 9th Highway and Urban Environment symposium - Rauch, Sébastien; Morrison, G.M.; Monzón, Andrés; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
The 9th Highway and Urban Environment Symposium (9HUES) was held in Madrid, Spain, from 9-11 June 2008. HUES is run by Chalmers University of Technology within the Alliance for Global Sustainability (The AGS). HUES was initiated by Professor Ron Hamilton at Middlesex Polytechnic (now University) in the early 1980s and had the title "Highway Pollution". The initial aim was to measure and assess challenges in highway pollution, with a strong emphasis on urban photochemical smog, ozone formation and particle release. After the first symposium, the emphasis on air pollution issues continued through to Munich in 1989 where diesel particulate issues and the relevance to health through measurements of PM10 emerged. The focus on air quality issues was also strengthened. In parallel, the symposium started to receive an increasing number of scientific contributions from the area of urban run off, indeed to the extent that the title of the symposium was changed to "Highway and Urban Pollution". Since then the importance of science in support of policy became increasingly important as a key aspect of the symposium. 9HUES was held at TRANSyT- Universidad Politécnica de Madrid, Spain to provide a professional and scientific forum on global examples of the science required to support pathways to a positive and sustainable future in the highway and urban environment. This volume contains papers grouped by topic on ustainable mobility and management; air pollution; trace elements in the environment; urban water contamination, contaminated sites and treatment; urban climate and climate change.
Sustainable mobility and management -- Planning for Sustainable Mobility with Personal Rapid Transit in Small European Cities -- Financing Urban Transport Through Value Capture -- Environmental Costs Account: A Base for Measuring Sustainability in Transport Plans -- A GIS Raster Model for Assessing the Environmental Quality of Spain Focused on SEA and Infrastructure Planning Procedures (LATINO Model) -- Sustainable Mobility in Metropolitan Areas -- Bases for Building a Sustainability Indicator System for Transport -- Air Pollution -- Biodiesel from Waste Olive Oil: Transesterification Kinetics, Exhaust Emissions and Fuel Consumption -- Intake Fraction for Benzene Traffic Emissions in Helsinki -- Modelling of Air Pollutants of Highway Roads in Hungary -- Seasonal Trend of Water-Soluble Ions at One TSP and Five PM2.5 Sampling Sites in Beijing, China -- Utilization of Meandering in a Receptor-Oriented Solution of the Line Source Dispersion Equation -- Measurements of Heavy Metals in Dry and Wet Deposition in São Paulo City -- Exposure of Cyclists to Ultra Fine Particles -- Air Pollution Exposure in an Unventilated Tunnel in Leeds, UK -- Assessment of Aerosol Concentration Sampled at Five Sites in Beijing from 2005 Till 2007 -- Emissions Pollutant from Diesel, Biodiesel and Natural Gas Refuse Collection Vehicles in Urban Areas -- Trace elements in the environment -- Platinum-Group Element Distribution in Hathersage, a Small Town Near Sheffield, UK: Evidence for a Single Source from Catalytic Converters -- Platinum and Lead in South African Road Dust -- Urban water contamination -- Reduction of Stormwater Runoff Toxicity by Wet Detention Ponds -- Microbial Contaminants Removal in a Stormwater Pond -- Reuse of Solid Waste from the Clearing of Road Basins and Ditches in Civil Engineering: Environmental Characterization, Ways of Treatment and Their Efficiency -- Methodology Used for Comparing Two Locations for the New Lisbon Airport Based on the Impacts on Surface Water -- Determination of Polycyclic Aromatic Hydrocarbons (PAHs) in Surface Waters and Runoff -- Use of Absorptive Media to Monitor Stormwater Contamination in Small Urban Drains -- Effects of Atmospheric Salt Deposition on Highway Runoff Characteristics – A Pilot Case Study -- Size Fractionation of Heavy Metals in Highway Runoff Waters -- Ecotoxicological Impacts on Brown Trout (Salmo trutta L.) Exposed to Runoff from a Four Lane Motorway in Norway -- Potential of Road Surface for a Non-point Source of Pollutants – Result of Nationwide Survey in Japan -- Trace Metals in Stockholm Sediments -- Environmental Impacts of the A6 Highway in La Silva Stream in the Region of Bierzo. (Leon). Spain -- Contaminated sites and treatment -- Arsenic Contamination After Wood Impregnation: Speciation, Sorption and Leaching -- Effect of Heavy Metal on Complex Permittivity Characteristics of Saturated Sand -- Blast-Furnace Sludge as Sorbent Material for Multi-metal Contaminated Water -- Evaluation of Zn, Cu and Pb Sorption-Desorption Phenomena in Kaolinite-Sand Media Filtration Pilot Scale Installation -- Diagnosing the Impact of Traffic on Roadside Soils Through Chemometric Analysis on the Concentrations of More Than 60 Metals Measured by ICP/MS -- Influence of De-Icing Salt on K Supply and Street Trees Ecological Status in Riga, Latvia -- Heavy Metals Soil Pollution in Some Urban Location from Romania -- Urban climate and climate change -- Effects of Transport Infrastructure Plans on Climate Change. Application to the Spanish Strategic Transport and Infrastructure Plan 2005–2020 (PEIT) -- Designing High Traffic Volume Urban Motorway Pavements to Maximize Sustainability -- Fuel Tax Levels Necessary to Achieve the Agreed Reduction Targets of CO2 Emissions. The Case of Madrid -- Emission Inventory for the Road Transport Sector in the Urban Area of Naples: Methodology and Results -- Transport Energy Use and Emission Trends in Spain.
Keywords: Environment; Air pollution; Environmental pollution; Water pollution; Environmental management; Environment, general; Atmospheric Protection/Air Quality Control/Air Pollution; Terrestrial Pollution; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Environmental Management